Climate change effects on agriculture in Tajikistan - Khakimov, Parviz; Aliev, Jovidon; Thomas, Timothy S.; Ilyasov, Jarilkasin; Pechtl, Sarah; Dunston, Shahnila (International Food Policy Research Institute, 2024)
Climate change is one of the main challenges for Tajikistan’s agricultural development in the medium and longer term. Tajikistan’s Agri-Food System and Sustainable Development Program (ASDP) for the period up to 2030 defined climate change as one of four key challenges to the development of agriculture and food systems. Accordingly, the Program accentuates the importance climate-optimized agriculture to ensure sustainable development of the sector.